Assessing differences in perceptions and actual health status: a national cross-sectional analysis - Ross, Kara (Kansas State University, 2010)
Public health policies seek to address health issues that pose significant concerns to public health policymakers. Because these initiatives have economic costs, economic agents’ response to them would be driven by the outcome of their benefit-cost assessment of the policies. Therefore, the congruence between perception and reality of economic agents’ health becomes important in evaluating the potential effectiveness of these initiatives. This research sought to determine the extent of congruence between objective and subjective health status at the individual level. The results would contribute to the framing and implementation of health policies that have higher probability of adoption by economic agents. The National Health and Nutrition Examination Survey (NHANES) 2005-2006 data were used for this research. The dependent variables defined in the study are subjective health status perception and objective metrics of individuals’ health status proxied by their body mass index (BMI), waist circumference, high density lipoprotein (HDL) cholesterol level, and fasting blood glucose. The nature of these dependent variables demanded that both categorical dependent variable and ordinary least squares models be employed in the estimation of the models. Chow tests were used to determine the extent of congruence between perception and reality of respondents’ health status. The study did not find any differences between perception and reality based on waist circumference but the same could not be said about BMI. Additionally, there were differences between subjective health perceptions and objective measures of health status based on receiving information about their health status from a health care professional. If it is assumed that the cost of responding to health policies are reduced with higher congruence between subjective and objective health status, then this study’s results suggest that policy must begin with increasing the objective information that people have about their health. While the provision of this information at the individual level could be expensive, it will improve the success rate of health promotion initiatives. The increase in these initiatives’ success should contribute to a reduction in the nation’s health care costs attributable to lifestyle related diseases such as obesity.
Keywords: Perception; Health status; Health information; Public health; Health Sciences, Public Health (0573)